Gender and development : theoretical, empirical, and practical approaches - Benería, Lourdes; Bisnath, Savitri (Edward Elgar Pub., 2001)
This two-volume set brings together a selection of the most significant contributions to the field of gender and development. The key emphasis is on economic analysis, with some articles informed by an interdisciplinary approach. The volumes cover a variety of topics, including conceptual and methodological questions, statistical accounting of women's work, issues related to the family, households and caring labour, poverty, employment and labour markets, structural adjustment policies and social change. The collection will be useful for economists as well as for other social scientists interested in the field of development, women's work, labor markets, and feminist economics. Although the volumes are addressed to an academic audience interested in development issues in general and gender and development in particular, they will also be of interest to government agencies, international organizations, NGOs and other institutions and individuals working on development, policy-making and action from a gender perspective.